KESENJANGAN LITERASI KEUANGAN BERDASARKAN GENDER PADA UMKM DI SURABAYA - Wiryakusuma, I Gusti Bagus Yosia; Handijaya, Elizabeth Maeko Cyrilla; Tasyavany, Rizky Nadia (Universitas Muhammadiyah Gresik, 2024)
Financial literacy is a basic need for everyone. Financial literacy is knowledge and skills in managing finances. In this study, financial literacy is represented by financial capability and financial knowledge. This study aims to see the differences in financial capability and financial knowledge based on gender. The independent t test was used to analyze the data. The results of the study show that there are differences in financial capability and financial knowledge based on gender. Other findings also found that the higher the financial knowledge, the higher the financial capability. Keyword: financial literacy, financial capability, financial knowledge, financial behavior